The Image of Religious Education in Galicia in the Second Half of the 19th Century in the Opinion of the Collaborators of Szkoła from Lviv - Wałęga, Agnieszka (Paedagogia Christiana, 2017)
The second half of the 19th century is the time of significant changes for Polish territories under Austrian rule. The autonomy obtained then allowed the educational system to develop, scientific and teachers’ circles to form unions, and the concept of national education to be put into practice. This education clearly appreciated the role of religion in shaping the national identity of Polish people. The aim of the article is to show how religious education was carried out in Galicia at that time at the lowest level of education, that is in community schools. The first Galician educational magazine Szkoła, published by teachers and educationalists organised in the Educational Research Association, was assumed as the primary source. The magazine, established in 1868, was mainly devoted to the problems of community schools, and the dissemination of the idea of national education was evident in its pages. Therefore the references to religious education could not go amiss. The collaborators of the magazine, well-known teachers and educationalists, including clergymen, responded to the problems of the relation between the Church and school, their legal determinants, pupils’ and teachers’ religious practices, the participation of teachers in religious education, or finally the assessment of catechisms and specific methodological instructions for catechists. Their opinions allow to recreate the image of Galician religious education in the second half of the 19th century.